Triple-Parameter Optimization of Linezolid 600mg Tablets: Dissolution, HPLC, and UV Spectrophotometric Evaluation - Syed Akif uddin; Lubna Bashir; Shazia Naz; Humera Naz; Hira Akther; Saima Yasin Baig; Faiza Akhtar (RADS Journal of Biological Research & Applied Science)
Aims and Objectives: The current research’s target is to obtain the dissolution profile of various brands of Linezolid 600 mg tablets available in Karachi, Pakistan and the assay was also performed using both the UV Spectrophotometric Technique and High Performance Liquid Chromatographic Techniques.